Pharmaceutical market, environmental public policies and water quality: the case of the São Paulo Metropolitan Region, Brazil - Rafaela Barbosa de Andrade Aragão; Décio Semensatto; Leandro Augusto Calixto; Geórgia Labuto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: Water pollution has been an increasing concern for the authorities responsible for planning and executing public policies. In this qualitative research, we have discussed the most sold pharmaceuticals in the São Paulo Metropolitan Region, Brazil, and compared public policies focused on pharmaceuticals and environmental issues among countries/regions. For that, data provided by Close-Up International related to the sales of medicines in the São Paulo Metropolitan Region between April/2016 and April/2017 were collected and processed to identify and quantify the pharmaceutical products. The 300 most sold medicines in the São Paulo Metropolitan Region fall in 26 therapeutic classes, which include 159 drugs. The most sold pharmaceutical products group is nonsteroidal anti-inflammatory drugs (NSAIDs) representing approximately 44.3% of the total. The ten most sold pharmaceuticals sum up 1200 tons. Dipyrone is the first place in mass representing around 488 tons, followed by metformin with around 310 tons commercialized. Public policies focused on pharmaceuticals in the environment still need adjustments to improve reinforcement, even in developed countries. There is no international standard on how to conduct the issue, each country adopting the public policy that best matches to the local. Brazil, despite having some legislation that approaches the theme, still lacks effective public policies and stakeholder awareness. In this aspect, the need for improvement of the reverse logistics system, consumer orientation to the adequate disposal of unused/expired medicines, and the adoption of the unit-dose system as a therapeutic strategy is evident.